1982
DOI: 10.1128/jcm.15.3.517-521.1982
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase immune electron microscopy-double-antibody technique for rapid detection of papovaviruses

Abstract: The solid-phase immune electron microscopy-double-antibody technique, which takes less than 1 h to perform, was applied as a rapid, sensitive, and specific diagnostic tool in the demonstration of papovavirus particles. BK virus propagated in 82C human skin fibroblasts and a monospecific high-titer immune serum to BK virus were used to establish the test procedure. When Formvar-carbon-coated grids were treated with appropriately diluted antibody, a 28-fold increase of virus particles per square micrometer was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Using SPIEM, the sensitivity of diagnostic EM is improved up to 100 times (Kjeldsberg and Mortensen-Egnund, 1982) and reaches detection limits down to values of e.g. 10 2 -10 3 plaque forming units per milliliter (Giraldo et al, 1982). Compared to nucleic acid amplification techniques (NAT) for SRSVs neither SPIEM nor NAT detect every virus-positive specimen-however, they complement each other (Humphrey et al, 1997;Cubitt et al, 1999).…”
Section: Methods Used In Diagnostic Emmentioning
confidence: 99%
“…Using SPIEM, the sensitivity of diagnostic EM is improved up to 100 times (Kjeldsberg and Mortensen-Egnund, 1982) and reaches detection limits down to values of e.g. 10 2 -10 3 plaque forming units per milliliter (Giraldo et al, 1982). Compared to nucleic acid amplification techniques (NAT) for SRSVs neither SPIEM nor NAT detect every virus-positive specimen-however, they complement each other (Humphrey et al, 1997;Cubitt et al, 1999).…”
Section: Methods Used In Diagnostic Emmentioning
confidence: 99%
“…Traditional methods for detecting and identifying polyomaviruses include serologic methods, virus isolation by cell culture and electron microscopy [Giraldo et al, 1982;Knowles et al, 1989;Nilsen et al, 1991]. Recently, several studies have shown PCR to be an effective tool for detecting polyomaviruses in a range of clinical samples Chang et al, 1996;De Santis and Azzi, 1996]; as a result, PCR is now emerging as the ''gold standard'' for polyomavirus detection.…”
Section: Introductionmentioning
confidence: 99%
“…Others have used SPIEMDAT (SPIEMDAGT without colloidal gold) for the detection of rotavirus (9) and papovavirus (5). In the former study, grids were precoated with protein A to facilitate antibody binding (9), while in the latter study no decorator antibody was employed (5). Papovavirus was detected by using the same antiserum for the capture and decorator antibodies (5).…”
Section: Discussionmentioning
confidence: 99%